2013
DOI: 10.5152/akd.2013.141
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Turkish version of the European Heart Failure Self-Care Behavior Scale

Abstract: Objective: The specific purpose of this study was to investigate the validity of the Turkish version of the European Heart Failure Self-care Behavior Scale by applying to 494 Turkish Heart Failure Patients. Methods: The study was conducted as a cross-sectional sample survey, between October 2012 and January 2013. The 494 patients who applied with a diagnosis of heart failure were included in the study after determining the clinical diagnosis and type of treatment. Cronbach's alpha coefficient was used to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
1
15
1
Order By: Relevance
“…Similar results were previously reported in studies which used the same approach for assessing discriminant validity of the scale. 5,8,18,19 The majority of previous studies demonstrated adequate internal consistency of the overall scale (both the 12-and 9-item) among different populations, with a Cronbach's alpha coefficient ranging from 0.68 to 0.93. 6,9,10,18e22 In the current study measures of internal consistency of the scale ranged between low and moderate.…”
Section: Discussionmentioning
confidence: 96%
“…Similar results were previously reported in studies which used the same approach for assessing discriminant validity of the scale. 5,8,18,19 The majority of previous studies demonstrated adequate internal consistency of the overall scale (both the 12-and 9-item) among different populations, with a Cronbach's alpha coefficient ranging from 0.68 to 0.93. 6,9,10,18e22 In the current study measures of internal consistency of the scale ranged between low and moderate.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding a single factor model, marginally acceptable fit of the EHFScBS single scale was obtained by CFA in the study evaluating Japanese version of the EHFScBS [17]. On the contrary, PCA based four component solution (Compliance to the treatment, Adherence to the activities, Adherence to the recommendations, Getting help) explaining 61% of variance was proposed by Baydemir et al [7]. The solution was further confirmed by CFA, but the reasons for the use of an exploratory approach in the first place were not clearly stated.…”
Section: Validitymentioning
confidence: 99%
“…The twelve-item scale has been validated in several languages; Jaarsma at al. [4] used pooled data of patients from Sweden, the Netherlands and Italy, later on validation studies of English [8], Japanese [17], Italian [27], Chinese [9], Brazilian Portuguese [26], Turkish [7] and Polish [28] versions of the scale were published. Psychometric properties of the nine-item scale were first tested in a pooled convenience sample of patients from Sweden, the Netherlands, the United Kingdom, Italy, Germany and Spain [10]; afterwards validation studies of German [12], English [11], Greek [14] and Italian [13] versions were published.…”
Section: Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Our study the total score of EHFScBS was 31,20±8, which was found to be 24. 8±7.6, 33.3±7.8, 32.6±9.1, 34.0±7.99 and 43,00±5,7 in the studies of Lupon et al (2008), Jaarsma et al (2003), Kato et al (2008), Baydemir et al (2013)and Asgar-Pour et al (2016). These differences might be resulted from the differences in the patient characteristics and health conditions.…”
Section: Discussionmentioning
confidence: 89%